MANAGEMENT IMPLEMENTATION OF EDUCATION AND TRAINING CENTER FOR STUDENT TRAINING CENTER (PPLM), KARATE BRANCH OF BANDA ACEH CITY - Yahya. A.K; Irfandi (Jurnal Ilmiah STOK Bina Guna Medan, 2020)
This research study aims to: (1) Know the organizational structure of the Banda Aceh City Grade Fighting Student Training Center (PPLM). ) Knowing the management of facilities and infrastructure in supporting the achievements of athletes in the Student Training Development Center (PPLM) to fight degrees in Banda Aceh City. (4) Knowing the implementation of financial management at the Student Training Development Center (PPLM) of the ranks of Banda Aceh City. (5) Knowing the implementation of training management at the Training Center for Student Training (PPLM) to fight degrees in Banda Aceh City. The research was carried out at the Center for Student Training Development (PPLM) to fight degrees in Banda Aceh City. This study uses a qualitative descriptive method. The unit of analysis is the Central Training Center for Student Training (PPLM) to fight degrees in the City of Banda Aceh. Data retrieval techniques through documentation study, in-depth interviews, and observation. Sources of data in this study are administrators, coaches, and athletes of the Banda Aceh City Student Training Development Center (PPLM). The results showed that: in general, the implementation of the management of the Student Training Development Center (PPLM) in Banda Aceh was generally very good.